“Antimicrobial Activity of the Latex of Jatropha Curcas Against Cutaneous Wound and Burns Infection” - Al-Shami AS; Alzomor M (Infection and Drug Resistance)
Ali Salman Al-Shami,1,2 Mokhtar Alzomor3 1Department of Pharmacology, Faculty of Medicine and Health Sciences, Sanaa University, Sanaa, Yemen; 2Jiblah University for Medical and Health Science, Ibb, Yemen; 3Department of Laboratory, Faculty of Medicine and Health Sciences, Alnasser University, Sanaa, YemenCorrespondence: Mokhtar Alzomor, Department of Laboratory, Faculty of Medicine and Health Sciences, Alnasser University, Sanaa, Yemen, Email alzomormokhtar33@gmail.comBackground: There is a growing interest in natural materials with antibacterial qualities as alternatives. Jatropha curcas latex has long been used to treat infections.Objective: Compare the antimicrobial activities of both Jatropha curcas latex and the used antibiotics against the isolated microorganisms which cause wound burn infection.Methods: An experimental study was carried out in Sana’a City, Yemen, to assess the antimicrobial properties of J. curcas latex. Infected burn wounds were found to contain pathogenic microorganisms such as Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Candida albicans. Standard antimicrobial strains were subjected to testing as well. We obtained latex from verified J. curcas specimens and subjected it to phytochemical analysis. The assessment of antimicrobial activity involved the use of agar well diffusion, disc diffusion, and broth dilution methods to establish inhibition zones and minimum inhibitory concentrations (MICs).Results: The phytochemical examination of J. curcas latex identified the presence of tannins, flavonoids, alkaloids, glycosides, sterols, saponins, and terpenes. The latex exhibited considerable antibacterial efficacy against all tested species, with inhibition zones measuring from 23 mm (K. pneumoniae) to 31.3 mm (S. aureus). The MIC values varied from 6.25 mg/mL (eg, E. coli, K. pneumoniae, C. albicans) to 25 mg/mL (S. aureus, P. aeruginosa). The comparative research indicated that J. curcas latex surpassed tetracycline and had equivalent or better efficacy to ofloxacin and fluconazole against several isolates.Conclusion: The latex of J. curcas has extensive antibacterial action against major burn wound pathogens. Its efficacy can be linked to the presence of several bioactive substances. These findings point to its potential use as a topical antibacterial agent in burn wound treatment, particularly in countries with significant antibiotic resistance.Keywords: Jatropha curcas, antimicrobial activity, latex, burn wound infection